Effects of Particle Size on Mechanical, Thermal and Morphological Properties of Untreated Nano and Micro Calcium Carbonate Powder [CaCO3] filled HDPE Polymer Composites - (:unkn) unknown (M D PUBLICATIONS, 2012)
High density polyethylene filled with particulate fillers is of great interest in both research and industry It is well known that HDPE has good processability allowing accepting different types of natural and synthetic fillers. As fillers, mica, kaolin, calcium carbonate and talc are the most often used to reduce both the production cost and to improve the properties of the thermoplastics, such as rigidity, strength, hardness, flexural modulus, dimensional stability, crystallinity, electrical and thermal conductivity. In this study, five kinds of calcium carbonate (CaCO3) with different particle sizes are chosen and mixed with HOPE polymer to investigate the effect of particle size on mechanical and morphological properties of composites. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, HOPE composites were subjected to examinations to obtain their tensile strengths, yield strengths, elasticity modulus, % elongation, Izod impact strength, hardness, HDT, MFI and Vicat softening point.
Keywords: Calcium carbonate; high density polyethylene; composites; particle size; CRYSTALLIZATION BEHAVIOR; NANOCOMPOSITES